THE CORRELATION BETWEEN STUDENTSâ FREQUENCY OF LISTENING TO ENGLISH SONGS AND THEIR LISTENING ACHIEVEMENT - Rosyida M. R., Elvira (JURNAL SMART, 2016)
This study is aimed at investigating whether there is a significant correlation between studentsâ frequency of listening to English songs and their listening achievement This study was conducted at the first year students of State Senior High School 9 Bandarlampung, Lampung. A descriptive quantitative was employed in this study which used ex-post facto design and the data were taken from questionnaire, semi-structured interview, and listening test. The data were analyzed by using Statistical Package for Social Science (SPSS) version 16.0. The hypothesis was tested by using Pearson Product Moment Correlation Coefficient. The test result showed that there is a significant correlation between studentsâ frequency of listening to English songs and their listening achievement. From the result of interview, it showed that most of the students believe that by having high frequency of listening to English songs, it helps them in recognizing the spoken language and get high score in listening ability.Keywords: listening to English song, listening ability, frequency of listening